A mutation in the Na-K-2Cl cotransporter-1 leads to changes in cellular metabolism - Omer, Salma (J Cell Physiol, 2020)
The Na-K-Cl cotransporter-1, NKCC1, by mediating the electroneutral transport of Na(+), K(+), and Cl(−) plays an important role in cell volume regulation, epithelial transport, and the control of neuronal excitability. Recently, we reported the first known human mutation in SLC12A2, the gene encoding NKCC1. The 17-year old patient suffers from multi-organ failure. Laboratory tests conducted on muscle and liver biopsies of the patient showed abnormal increase in mitochondrial DNA copy number and increased glycogen levels, indicating the possibility that the transporter may play a role in energy metabolism. Here, we show that fibroblasts isolated from the patient demonstrate a significant increase in mitochondrial respiration, compared to fibroblasts isolated from healthy individuals. Similarly, MDCK cells transfected with EGFP-tagged mutant NKCC1 DNA demonstrated increased mitochondrial respiration when compared to MDCK cells expressing EGFP-tagged wild-type cotransporter. Direct inhibition of the cotransporter through addition of bumetanide did not change the rate of basal respiration, but led to increased maximal mitochondrial respiration. Fibroblasts extracted from NKCC1(WT/DFX) and NKCC1(DFX/DFX) mice also demonstrated a significant elevation in mitochondrial respiration, compared to fibroblasts isolated from their wild-type littermates. Expression of the mutant protein was associated with an increase in hydrogen peroxide and peroxidase activity and a decrease in mRNA transcript levels for protein involved in the unfolded protein response (UPR). These data reveal that cells expressing the mutant cotransporter demonstrate increased mitochondrial respiration and behave like they are experiencing a state of starvation.